2021
DOI: 10.3390/diagnostics11091654
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Electronic Portal Imaging Device Dosimetry Method

Abstract: Support arm backscatter and off-axis effects of an electronic portal imaging device (EPID) are challenging for radiotherapy quality assurance. Aiming at the issue, we proposed a simple yet effective method with correction matrices to rectify backscatter and off-axis responses for EPID images. First, we measured the square fields with ionization chamber array (ICA) and EPID simultaneously. Second, we calculated the dose-to-pixel value ratio and used it as the correction matrix of the corresponding field. Third,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Our team conducted earlier research on pre-treatment dose verification based on EPID [ 25 ] and in vivo dose verification methods [ 25 , 26 ], discovering that EPID transmission images contain patient anatomical information, which can be utilized for reconstructing the three-dimensional structure of patients. Furthermore, the radiation source used for EPID image acquisition is the same as that used during patient treatment, which addresses the limitations of CBCT for positioning verification to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Our team conducted earlier research on pre-treatment dose verification based on EPID [ 25 ] and in vivo dose verification methods [ 25 , 26 ], discovering that EPID transmission images contain patient anatomical information, which can be utilized for reconstructing the three-dimensional structure of patients. Furthermore, the radiation source used for EPID image acquisition is the same as that used during patient treatment, which addresses the limitations of CBCT for positioning verification to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic portal imaging devices (EPIDs), primarily used for pretreatment checks in intensity‐modulated radiation therapy (IMRT) and volumetric‐modulated arc therapy (VMAT), are gaining use for in‐vivo dosimetry. 1 , 2 Studies analyzing the effectiveness of EPIDs in detecting clinically reported incidents have found that when used for pretreatment quality assurance (QA), EPIDs detect a low number of clinically reported incidents (6%). 3 However, they are much more effective when used in‐vivo QA.…”
Section: Introductionmentioning
confidence: 99%